A chassis catalyst for reducing HC emissions from gasoline engine exhaust

By using honeycomb ceramic carrier chassis catalyst containing Pd and Rh coatings in gasoline engine exhaust, the cold start HC emission problem is solved, the HC emissions of the whole vehicle are reduced, the pressure of tight coupling/manifold catalyst is reduced, and the pressure of the tightly coupled/manifold catalyst is reduced, and the Cost improves market competitiveness.

CN115888810BActive Publication Date: 2024-12-13YIBIN COWIN AUTO CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202211440442.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2024-12-13
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The prior art has difficulties in reducing the exhaust HC emissions of gasoline engines, especially during cold start-up, the precious metal usage design of the tightly coupled/manifold catalyst TWC is difficult to meet the requirements of rapid ignition, and the influence of the chassis catalyst is ignored, resulting in the HC emission pressure. Large, cost increases.

Method used

Using a chassis catalyst including a honeycomb ceramic support containing Pd and Rh coatings, the Pd coating is used to perform physical and chemical adsorption of HC at low temperatures and at high temperatures by combining modified multi-cyclic molecular sieve and oxide additives. The lower Rh coating is further oxidized to achieve desorption and oxidation of HC, thereby reducing overall HC emissions.

Benefits of technology

It effectively reduces the HC emissions of the whole vehicle, reduces the pressure of the tightly coupled/manifold catalyst TWC to cope with cold start emissions, reduces the cost of converter, improves the market competitive advantage, and reduces the pressure of engine calibration optimization work.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888810B_ABST
    Figure CN115888810B_ABST
Patent Text Reader

Abstract

The invention provides a chassis catalyst for reducing HC emission of gasoline engine exhaust. The chassis catalyst comprises: a Pd-containing coating layer, a Rh-containing coating layer, and a honeycomb ceramic carrier; the Pd-containing coating layer is coated on the surface of the honeycomb ceramic carrier, and the Rh-containing coating layer is coated on the surface of the Pd-containing coating layer; the raw material for forming the Pd-containing coating layer contains a modified polycyclic molecular sieve; the chassis catalyst is used to solve the HC emission problem of some cold starts, greatly reduce the HC emission of gasoline engine exhaust, and can achieve the effect of comprehensive treatment of gasoline engine exhaust when used in conjunction with a tight-coupled / manifold catalyst TWC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic catalytic materials, and in particular relates to a chassis catalyst for reducing HC emissions from gasoline engine tail gas. Background Art

[0002] With the country's increasingly stringent vehicle emission requirements and the implementation of China's sixth-stage automobile exhaust emission regulations, in addition to requiring engine technology upgrades and vehicle matching technology improvements, post-treatment catalyst technology has been posed with severe challenges.

[0003] The National VI stage emission regulations have added emission requirements for PN and N2O, and the emission operating conditions have changed from the fifth stage steady-state conditions (NEDC cycle) to the sixth stage transient conditions (WLTC cycle). The limits on gaseous pollutants emitted by automobiles have been significantly tightened, among which the emission of gaseous pollutants HC is even more difficult. HC emissions mainly depend on the ignition activity of the cold start catalyst. In order to solve the cold start HC problem, in addition to requiring the close-coupled / manifold catalyst TWC to be arranged as close to the engine as possible, the precious metal content of the close-coupled / manifold catalyst TWC is also required to be designed to be very high in order to meet the rapid ignition requirements of the catalyst. However, with the increase in market cost and competitive pressures on automobile companies, catalyst costs are often limited. At this time, after the amount of precious metals is fixed, the pressure to meet HC emissions requirements becomes very high.

[0004] The cost-effective close-coupled / manifold catalyst TWC in the prior art is relatively weak in HC cold-start purification capability. Most of the ideas for solving cold-start HC emissions in the prior art are to improve the capability of the close-coupled / manifold catalyst TWC, but often ignore the impact of the chassis catalyst on cold-start HC emissions. Summary of the invention

[0005] The purpose of the present invention is to provide a chassis catalyst for reducing HC emissions from gasoline engine exhaust. The chassis catalyst is used to solve some HC emission problems during cold start, significantly reduce HC emissions from gasoline engine exhaust, and can achieve the effect of comprehensive treatment of gasoline engine exhaust when used in conjunction with a close-coupled / manifold catalyst TWC.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A chassis catalyst for reducing HC emissions from gasoline engine exhaust, the chassis catalyst comprising: a first Pd-containing coating, a second Rh-containing coating, and a honeycomb ceramic carrier; the first Pd-containing coating is coated on the surface of the honeycomb ceramic carrier, and the second Rh-containing coating is coated on the surface of the first Pd-containing coating; the raw material for forming the first Pd-containing coating contains a modified polycyclic molecular sieve.

[0008] The Pd concentration in the Pd-containing coating is 0.1-20 g / cft.

[0009] The Rh concentration in the second Rh-containing coating is 0.1-10 g / cft.

[0010] The slurry A for forming the Pd-containing coating comprises the following raw materials: modified low-zirconium-content cerium-zirconium powder, modified alumina, modified polycyclic molecular sieve, oxide additive, Pd, and water; wherein the zirconium oxide content in the modified low-zirconium-content cerium-zirconium powder is 20-49.5%.

[0011] The coating amount of each raw material in slurry A per liter of honeycomb ceramic carrier is as follows: modified low zirconium content cerium zirconium powder 1-100g, modified alumina 1-100g, modified polycyclic molecular sieve 1-250g, oxide additive 1-45g, Pd 0.1-20g / cft.

[0012] The slurry B for forming the second Rh-containing coating includes the following raw materials: modified cerium zirconium powder with high zirconium content, modified zirconium oxide, modified aluminum oxide, water, and Rh; wherein the zirconium oxide content in the modified cerium zirconium powder with high zirconium content is 50-70%.

[0013] The concentrations of the raw materials in the slurry B are as follows: 1-50 g / L of modified high zirconium content cerium zirconium powder, 1-50 g / L of modified zirconium oxide, 1-100 g / L of modified aluminum oxide, and 1-45 g / L of oxide additive.

[0014] The coating amount of slurry A per liter of honeycomb ceramic carrier is 1-1000 g, and the Pd concentration in the Pd coating formed after coating is 0.1-20 g / cft.

[0015] The coating amount of slurry B per liter of honeycomb ceramic carrier is 1-500 g, and the Rh concentration in the Rh-containing coating layer II formed after coating is 0.1-10 g / cft.

[0016] The modified polycyclic molecular sieve is a polycyclic molecular sieve modified with any one or more elements of Pd, Pt, Rh, Cu, Fe, Mn, and Co; the content of the modified component in the modified polycyclic molecular sieve is 0.01-20 g / cft; the polycyclic molecular sieve in the modified polycyclic molecular sieve is one or more of BEA, CHA, MOR, MFI, LTA, FAU, MON, AFN, AFT, and AFX type molecular sieves.

[0017] The modified low zirconium content cerium-zirconium powder is a low zirconium content cerium-zirconium powder modified by any one or more elements of La, Ba, Y, Pr, Sn, and Nd, and the content of the modified component in the modified low zirconium content cerium-zirconium powder is 0.1-30%.

[0018] The modified high zirconium content cerium-zirconium powder is a high zirconium content cerium-zirconium powder modified by any one or more elements of La, Ba, Y, Pr, Sn, and Nd, and the content of the modified component in the modified high zirconium content cerium-zirconium powder is 0.1-30%.

[0019] The modified zirconium oxide is zirconium oxide modified by any one or more elements of La, Ba, Y, Pr, Sn and Nd, and the content of the modified component in the modified zirconium oxide is 0.1-40%.

[0020] The oxide additive is any one or more oxides of Sn, Y, Pr, La, Nd, Ba, Sr, Ce, and Ca.

[0021] The modified alumina is alumina modified by any one or more elements of Y, La, Si, Ce, Sr, K, Li, Mg, Sn, and Na, and the content of the modified component in the modified alumina is 10-30%.

[0022] The chassis catalyst provided by the present invention realizes low-temperature adsorption of HC by physical and chemical adsorption of HC by the modified multi-ring molecular sieve in the Pd-containing coating layer 1 coated on the surface of the honeycomb ceramic carrier. When the temperature rises to above 250°C, the chassis catalyst oxidizes HC, and the unoxidized HC desorbs and diffuses to the Rh-containing coating layer 2 to be further oxidized, thereby realizing high-temperature desorption and oxidation. The chassis catalyst provided by the present invention can greatly reduce the pressure of the close-coupled / manifold catalyst TWC to cope with cold start emissions, and effectively improve the overall purification effect of HC.

[0023] Compared with the prior art, the chassis catalyst provided by the present invention has the following beneficial effects:

[0024] 1. Can effectively reduce the HC emissions of the whole vehicle;

[0025] 2. It can effectively reduce the pressure of close-coupled / manifold catalyst TWC to deal with cold start emissions;

[0026] 3. It can significantly reduce the cost of converters and improve market competitiveness;

[0027] 4. Reduce the pressure of engine calibration optimization work. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a second-sampled concentration diagram of pollutants emitted from gasoline engine exhaust after the chassis catalyst in Example 1 and Comparative Example 1 is applied;

[0029] Figure 2 It is the percentage of gasoline engine exhaust pollutant emissions after the chassis catalyst in Example 1 and Comparative Example 1 is applied. DETAILED DESCRIPTION

[0030] A chassis catalyst for reducing HC emissions from gasoline engine exhaust, the chassis catalyst comprising: a first Pd-containing coating, a second Rh-containing coating, and a honeycomb ceramic carrier; the first Pd-containing coating is coated on the surface of the honeycomb ceramic carrier, and the second Rh-containing coating is coated on the surface of the first Pd-containing coating; the raw material for forming the first Pd-containing coating contains a modified polycyclic molecular sieve.

[0031] The Pd concentration in the Pd-containing coating is 0.1-20 g / cft.

[0032] The Rh concentration in the second Rh-containing coating is 0.1-10 g / cft.

[0033] The slurry A for forming the Pd-containing coating comprises the following raw materials: modified low-zirconium-content cerium-zirconium powder, modified alumina, modified polycyclic molecular sieve, oxide additive, Pd, and water; wherein the zirconium oxide content in the modified low-zirconium-content cerium-zirconium powder is 20-49.5%.

[0034] The concentration of each raw material in the slurry A is as follows: 1-100 g / L of modified low zirconium content cerium zirconium powder, 1-100 g / L of modified alumina, 1-250 g / L of modified polycyclic molecular sieve, and 1-45 g / L of oxide additive, wherein the zirconium oxide content in the modified low zirconium content cerium zirconium powder is 20-49.5%.

[0035] The slurry B for forming the second Rh-containing coating includes the following raw materials: modified cerium zirconium powder with high zirconium content, modified zirconium oxide, modified aluminum oxide, water, and Rh; wherein the zirconium oxide content in the modified cerium zirconium powder with high zirconium content is 50-70%.

[0036] The concentrations of the raw materials in the slurry B are as follows: 1-50 g / L of modified high zirconium content cerium zirconium powder, 1-50 g / L of modified zirconium oxide, 1-100 g / L of modified aluminum oxide, and 1-45 g / L of oxide additive.

[0037] The modified polycyclic molecular sieve is a polycyclic molecular sieve modified by any one or more elements of Pd, Pt, Rh, Cu, Fe, Mn, and Co; the content of the modified component in the modified polycyclic molecular sieve is 0.1-10%; the polycyclic molecular sieve in the modified polycyclic molecular sieve is one or more of BEA, CHA, MOR, MFI, LTA, FAU, MON, AFN, AFT, and AFX type molecular sieves.

[0038] The modified cerium-zirconium powder with low zirconium content is a cerium-zirconium powder with low zirconium content modified by any one or more elements of La, Ba, Y, Pr, Sn and Nd, and the content of the modified component in the modified cerium-zirconium powder with low zirconium content is 0.1-30%.

[0039] The modified cerium-zirconium powder with high zirconium content is a cerium-zirconium powder with high zirconium content modified by any one or more elements of La, Ba, Y, Pr, Sn and Nd, and the content of the modified component in the modified cerium-zirconium powder with high zirconium content is 0.1-30%.

[0040] The modified zirconium oxide is zirconium oxide modified by any one or more elements of La, Ba, Y, Pr, Sn and Nd, and the content of the modified component in the modified zirconium oxide is 0.1-40%.

[0041] The oxide auxiliary agent is one or more oxides of Sn, Y, Pr, La, Nd, Ba, Sr, Ce, and Ca.

[0042] The modified alumina is alumina modified with any one or more elements of Y, La, Si, Ce, Sr, K, Li, Mg, Sn, and Na, and the content of the modified component in the modified alumina is 10-30%.

[0043] The coating amount of slurry A per liter of honeycomb ceramic carrier is 1-1000 g, and the Pd concentration in the Pd coating formed after coating is 0.1-20 g / cft.

[0044] The coating amount of slurry B per liter of honeycomb ceramic carrier is 1-500 g, and the Rh concentration in the Rh-containing coating layer II formed after coating is 0.1-10 g / cft.

[0045] The modified polycyclic molecular sieve is prepared by an ion replacement method, and the modified low zirconium content cerium zirconium powder, the modified high zirconium content cerium zirconium powder, the modified zirconium oxide, and the modified aluminum oxide are all prepared by a coprecipitation method, as follows:

[0046] The preparation method of Pd modified polycyclic molecular sieve comprises the following steps:

[0047] Step 1: Add water into the reactor, start stirring, set the stirring rate to 800 rpm, then gradually add the polycyclic molecular sieve, disperse evenly, calculate the powder content to be 35%, start the heating program, and set the constant temperature to 45°C;

[0048] Step 2: Calculate the amount of precious metal Pd solution to be added according to the required amount of precious metal Pd and place it in a beaker. Keep the beaker at a constant temperature of 45°C, and add triethanolamine to disperse the precious metal. Stir while adding dropwise. The stirring speed is set to 100 rpm. The mass of precious metal Pd solution: mass of triethanolamine = 1:1. After the addition of triethanolamine is completed, continue stirring for 0.5h and let it stand to cool to room temperature.

[0049] Step 3: Set the peristaltic pump rate to 2 mL / min, add the dispersed precious metal Pd solution to the dispersed polycyclic molecular sieve aqueous solution through the peristaltic pump, and control the aqueous solution at a constant temperature of 45°C. During the addition process, adjust the pH value of the solution in the reactor to 7 by adding an appropriate amount of ammonium bicarbonate solution. After the addition is completed, continue to stir at a constant temperature of 45°C for 24 hours for ion exchange;

[0050] Step 4: After the exchange is completed, filter and wash with deionized water three times. After washing, place it in an oven at 120°C for 12 hours, and finally place it in a calcination furnace for 2 hours. The calcination temperature is 600°C and the heating condition is 5°C / min.

[0051] The preparation method of modified low zirconium content cerium zirconium powder and modified high zirconium content cerium zirconium powder comprises the following steps:

[0052] Step 1: The cerium precursor is cerium nitrate hydrate, the zirconium precursor is zirconium oxynitrate hydrate, the modifying substance precursors are all nitrate hydrates, the dispersant is polyethylene glycol, and the precipitant is ammonium bicarbonate. The amount of modified substance added is calculated according to the proportion of the modified substance in the modified cerium zirconium powder, and the amounts of cerium and zirconium in the modified cerium zirconium powder are calculated separately and converted into the amount of nitrate precursor.

[0053] Step 2: Add an appropriate amount of water to the reaction kettle, and add zirconium oxynitrate hydrate, cerium nitrate hydrate, and modified substance precursor nitrate hydrate respectively, stir and fully dissolve them to prepare a precursor mother solution with a total metal ion molar concentration of 0.5 mol / L;

[0054] Step 3: Add 1% polyethylene glycol to the prepared precursor mother solution and stir for 0.5h to disperse;

[0055] Step 4: Heat the solution dispersed in step 3 and maintain the solution at a constant temperature of 80°C;

[0056] Step 5: prepare ammonium bicarbonate precipitant solution, the molar amount of ammonium bicarbonate is 5 times the molar amount of total metal ions in the precursor mother solution, and control the solution pH value to 10;

[0057] Step 6: Set the stirring speed of the precursor mother liquor to 100 rpm, set the peristaltic pump speed to 2 mL / min, and add the ammonium bicarbonate solution to the precursor mother liquor through the peristaltic pump until the pH of the solution is 8. Continue stirring for 0.5 h. Stop stirring when the pH does not change, and age overnight.

[0058] Step 7: filtering the solution that has been aged overnight, and washing the filtrate 3 times to obtain a cerium-zirconium composite precipitate;

[0059] Step 8: drying the cerium-zirconium composite precipitate in an oven at 120° C. for 12 hours, and then crushing it in a crusher;

[0060] Step 9: calcining the crushed cerium-zirconium composite precipitate in a calcining furnace at a heating rate of 5°C / min, a calcining temperature of 1000°C, and a calcining time of 4h to obtain modified cerium-zirconium powder;

[0061] When the nitrate hydrate of the modifying material precursor is selected as any one or more of the nitrate hydrates of La, Ba, Y, Pr, Sn, and Nd, low zirconium content cerium-zirconium powder modified with any one or more of La, Ba, Y, Pr, Sn, and Nd or high zirconium content cerium-zirconium powder modified with any one or more of La, Ba, Y, Pr, Sn, and Nd can be prepared.

[0062] When the cerium nitrate hydrate and zirconium oxynitrate hydrate in the above method are replaced by zirconium nitrate hydrate, modified zirconium oxide can be prepared.

[0063] When the cerium nitrate hydrate and zirconium oxynitrate hydrate in the above method are replaced by aluminum nitrate hydrate, modified alumina can be prepared.

[0064] The present invention is described in detail below with reference to the embodiments.

[0065] Example 1

[0066] A chassis catalyst TWC2-2 for reducing HC emissions from gasoline engine exhaust, the chassis catalyst consisting of a Pd-containing coating layer one, a Rh-containing coating layer two, and a honeycomb ceramic carrier; the Pd-containing coating layer one is coated on the surface of the honeycomb ceramic carrier, and the Rh-containing coating layer two is coated on the surface of the Pd-containing coating layer one; the raw material for forming the Pd-containing coating layer one contains a modified polycyclic molecular sieve.

[0067] The Pd concentration in the Pd-containing coating is 4 g / cft.

[0068] The Rh concentration in the second Rh-containing coating is 2 g / cft.

[0069] The specifications of the honeycomb ceramic carrier are: diameter 118.4mm, length 120mm, number of holes 400 mesh, and wall thickness 4mil.

[0070] The slurry A for forming the Pd-containing coating includes the following raw materials: cerium zirconium powder with low zirconium content modified by three elements of La, Pr and Nd, alumina modified by two elements of Y and La, polycyclic molecular sieve modified by Pd, BaO, SrO, Pd and water; wherein the zirconium oxide content in the cerium zirconium powder with low zirconium content modified by three elements of La, Pr and Nd is 35%.

[0071] The concentrations of the raw materials in slurry A are as follows: 50 g / L of cerium-zirconium powder with low zirconium content modified by three elements of La, Pr and Nd, 50 g / L of alumina modified by two elements of Y and La, 53 g / L of polycyclic molecular sieve modified by Pd, 10 g / L of BaO, and 15 g / L of SrO;

[0072] In the cerium-zirconium powder with low zirconium content modified by three elements La, Pr and Nd, the contents of La, Pr and Nd in the modified cerium-zirconium powder with low zirconium content are 5%, 8% and 5% respectively;

[0073] In the Y and La modified alumina, the contents of Y and La in the modified alumina are both 5%;

[0074] The content of Pd in ​​the Pd-modified multi-ring molecular sieve is 3 g / cft. The multi-ring molecular sieve is a mixture of BEA type molecular sieve and MFI type molecular sieve. The mass ratio of BEA type molecular sieve to MFI type molecular sieve is 2:1.

[0075] The slurry B for forming the Rh-containing coating II includes the following raw materials: cerium zirconium powder with high zirconium content modified by two elements La and Nd, zirconium oxide modified by three elements La, Pr and Nd, La-modified alumina, BaO, water and Rh; wherein the content of cerium zirconium powder with high zirconium content modified by two elements La and Nd is 65%.

[0076] The concentrations of the raw materials in slurry B are as follows: 28 g / L of cerium zirconium powder with high zirconium content modified by two elements La and Nd, 10.5 g / L of zirconium oxide modified by three elements La, Pr and Nd, 28 g / L of La-modified alumina, and 10 g / L of BaO;

[0077] In the cerium-zirconium powder with high zirconium content modified by La and Nd, the content of La and Nd in the modified cerium-zirconium powder with high zirconium content is 5%;

[0078] In the La, Pr and Nd modified zirconia, the contents of La, Pr and Nd in the modified zirconia are all 10%;

[0079] In the La-modified alumina, the content of La in the modified alumina is 10%.

[0080] The method for preparing the chassis catalyst TWC2-2 for reducing HC emission from gasoline engine exhaust comprises the following steps:

[0081] (1) Slurry A preparation steps

[0082] Step 1: Add La, Pr, Nd three elements modified low zirconium content cerium zirconium powder into water, the mass ratio of La, Pr, Nd three elements modified low zirconium content cerium zirconium powder to water is 45:55, and stir for 0.5h to mix evenly to obtain mixed solution 1; add Y and La two elements modified alumina into water, the mass ratio of Y and La two elements modified alumina to water is 45:55, and stir for 0.5h to mix evenly to obtain mixed solution 2; and mix mixed solution 1 and mixed solution 2, continue stirring for 0.5h, and then pass into a sand mill for ball milling, and ball milling to a slurry particle size of 3-5um;

[0083] Step 2: Pd solution is added dropwise to the slurry in step 1 at a rate of 1 mL / min by a peristaltic pump. The slurry in step 1 is stirred while the Pd solution is added dropwise. The stirring speed is controlled at 500 rpm. After the addition of the Pd solution is completed, stirring is continued for 1 hour.

[0084] Step 3: Add Pd-modified polycyclic molecular sieve, BaO and SrO to the slurry in step 2 in sequence, control the stirring speed to 800 rpm, and continue for 1 hour;

[0085] Step 4: In step 3, a small amount of water is added to adjust the solid content of the slurry to 40% to obtain slurry A.

[0086] (2) Slurry B preparation steps:

[0087] Step 1: Add La and Nd modified cerium zirconium powder with high zirconium content and La, Pr and Nd modified zirconium oxide into water in sequence, control the solid content to 45%, and stir for 0.5h to mix evenly;

[0088] Step 2: The Rh solution is added dropwise to the slurry in step 1 at a rate of 1 mL / min by a peristaltic pump. The slurry in step 1 is stirred while the Rh solution is added dropwise. The stirring speed is controlled at 500 rpm. After the Rh solution is added dropwise, the stirring is continued for 1 hour.

[0089] Step 3: Add La-modified alumina to the slurry of step 2, control the stirring speed to 800 rpm, continue stirring for 0.5 h, then pass into a sand mill for ball milling until the slurry particle size is 3-5 um;

[0090] Step 4: BaO is added to the slurry of step 3, and a small amount of water is added to adjust the solid content of the slurry to 35%, to obtain slurry B;

[0091] (3) Chassis catalyst TWC2-2 production:

[0092] Step 1: Place the honeycomb ceramic carrier on the unloading device, and place a loading mold with an inner diameter of 120 mm on one end of the honeycomb ceramic carrier to hold the coating slurry;

[0093] Step 2: Set the negative pressure of the unloading equipment to 60KPa, pour slurry A into the loading mold with a container, and after the slurry is spread out by itself, start the unloading equipment to coat. The coating amount of slurry A per liter of honeycomb ceramic carrier is 600g, and the Pd concentration of the Pd coating formed after coating is 4g / cft;

[0094] Step 3: Remove the loading mold, place the coated honeycomb ceramic carrier in a hot air oven for drying, set the hot air oven parameters, turn on the ventilation function, the drying time is 8 hours, and the drying temperature is 120°C;

[0095] Step 4: Repeat steps 1-3 on the dried honeycomb ceramic carrier to coat the slurry B. The coating amount of the slurry B per liter of the honeycomb ceramic carrier is 300 g. The Rh concentration of the Rh coating layer formed after coating is 2 g / cft.

[0096] Step 5: Place the honeycomb ceramic carrier that has been coated twice and dried twice into a calcination furnace for calcination. Set the calcination conditions as follows: a heating rate of 5°C / min, a calcination temperature of 550°C, and a holding time of 4h. After calcination, a chassis catalyst TWC2-2 is obtained, and its precious metal concentrations Pd and Rh are 4g / cft and 2g / cft, respectively.

[0097] Comparative Example 1

[0098] A chassis catalyst TWC2-1, the chassis catalyst consists of a Pd-containing coating layer, a Rh-containing coating layer, and a honeycomb ceramic carrier; the Pd-containing coating layer is coated on the surface of the honeycomb ceramic carrier, and the Rh-containing coating layer is coated on the surface of the Pd-containing coating layer.

[0099] The Pd concentration in the Pd-containing coating is 4 g / cft.

[0100] The Rh concentration in the second Rh-containing coating is 2 g / cft.

[0101] The specifications of the honeycomb ceramic carrier are diameter 118.4mm, length 120mm, number of holes 400 mesh, and wall thickness 4mil.

[0102] The slurry A for forming the Pd-containing coating includes the following raw materials: cerium zirconium powder with low zirconium content modified by three elements La, Pr and Nd, alumina modified by two elements Y and La, BaO, SrO, Pd and water; wherein the zirconium oxide content in the cerium zirconium powder with low zirconium content modified by three elements La, Pr and Nd is 35%.

[0103] The concentrations of the raw materials in slurry A are as follows: 76.5 g / L of cerium-zirconium powder with low zirconium content modified by three elements of La, Pr and Nd, 76.5 g / L of alumina modified by two elements of Y and La, 10 g / L of BaO, 15 g / L of SrO, and 4 g / cft of Pd;

[0104] In the cerium-zirconium powder with low zirconium content modified by three elements La, Pr and Nd, the contents of La, Pr and Nd in the modified cerium-zirconium powder with low zirconium content are 5%, 8% and 5% respectively;

[0105] In the Y and La modified alumina, the contents of Y and La in the modified alumina are both 5%;

[0106] The slurry B for forming the second Rh-containing coating is the same as that in Example 1.

[0107] The method for preparing the chassis catalyst TWC2-1 for reducing HC emission from gasoline engine exhaust comprises the following steps:

[0108] (1) Slurry A preparation steps

[0109] Step 1: Add the cerium-zirconium powder with low zirconium content modified by La, Pr and Nd into water, the mass ratio of the cerium-zirconium powder with low zirconium content modified by La, Pr and Nd to water is 45:55, and stir for 0.5h to mix evenly; add alumina modified by Y and La into water, the mass ratio of alumina modified by Y and La to water is 45:55, and stir for 0.5h to mix evenly; and mix the modified cerium-zirconium powder slurry with high zirconium content and the modified alumina slurry, continue stirring for 0.5h, and then pass into a sand mill for ball milling, and ball mill to the slurry particle size of 3-5um;

[0110] Step 2: Pd solution was added dropwise to the slurry in step 1 at a rate of 1 mL / min by a peristaltic pump. The slurry in step 1 was stirred while the Pd solution was added dropwise. The stirring speed was controlled at 500 rpm. After the addition of the Pd solution was completed, stirring was continued for 1 hour.

[0111] Step 3: In the slurry of step 2, BaO and SrO were stirred at a speed of 800 rpm for 1 h.

[0112] Step 4: In step 3, a small amount of water is added to adjust the solid content of the slurry to 40% to obtain slurry A.

[0113] (2) The preparation steps of slurry B are the same as those in Example 1.

[0114] The preparation process of chassis catalyst TWC2-2 is the same as that of Example 1. After calcination, chassis catalyst TWC2-2 is obtained, and its precious metal concentration Pd is 4 g / cft, and Rh is 2 g / cft.

[0115] Test Case

[0116] The chassis catalyst TWC2-2 in Example 1 and the chassis catalyst TWC2-1 in Comparative Example 1 were both applied to a 1.5T gasoline vehicle model to test the second-collection data of pollutants and the emission results of pollutants. The second-collection data of pollutants are as follows: Figure 1 The emission results of pollutants are shown in Figure 2 As shown in Table 1. The sampling of pollutants is carried out in accordance with the national standard GB18352.6-2016, and the emission test of pollutants is carried out in accordance with the national standard GB18352.6-2016.

[0117] Catalyst selection route: close-coupled catalyst TWC1 + chassis catalyst TWC2, with a total precious metal content of 1.48g.

[0118] The tightly coupled catalyst TWC1 has the following characteristics: the ceramic carrier specification is 101.6*123.3 / 750-2.5, the precious metal concentration is 34g / cft, and Pt / Pd / Rh in the precious metals is 0 / 31.5 / 2.5.

[0119] The tightly coupled catalyst TWC1 is coated on the carrier in zones, and the zones are as follows: 41.1 mm in front of the ceramic carrier, the precious metal concentration is 90 g / cft, and Pt / Pd / Rh=0 / 87.5 / 2.5; 82.2 mm behind the ceramic carrier, the precious metal concentration is 6 g / cft; Pt / Pd / Rh=0 / 3.5 / 2.5; the Pd coating is coated on the lower layer of the ceramic carrier in an amount of 120 g / L, and the Rh coating is coated on the upper layer of the ceramic carrier in an amount of 80 g / L.

[0120] The pollutant data comparison after application of TWC2-1 in Comparative Example 1 and TWC2-2 in Example 1 is shown in Table 1.

[0121] Table 1

[0122]

[0123]

[0124] The above-mentioned detailed description of a chassis catalyst for reducing HC emissions from gasoline engine exhaust with reference to the embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A chassis catalyst for reducing HC emissions from gasoline engine exhaust. It is characterized in that The chassis catalyst comprises: a Pd-containing coating layer 1, a Rh-containing coating layer 2, and a honeycomb ceramic carrier; the Pd-containing coating layer 1 is coated on the surface of the honeycomb ceramic carrier, and the Rh-containing coating layer 2 is coated on the surface of the Pd-containing coating layer 1; the raw material for forming the Pd-containing coating layer 1 contains a modified polycyclic molecular sieve; The Pd concentration in the first Pd-containing coating is 0.1-20 g / cft; the Rh concentration in the second Rh-containing coating is 0.1-10 g / cft; The slurry A for forming the Pd-containing coating 1 includes the following raw materials: modified low-zirconium-content cerium-zirconium powder, modified alumina, modified polycyclic molecular sieve, oxide additive, Pd, and water; wherein the zirconium oxide content in the modified low-zirconium-content cerium-zirconium powder is 20-49.5%; the modified low-zirconium-content cerium-zirconium powder is a low-zirconium-content cerium-zirconium powder modified by any one or more elements of La, Ba, Y, Pr, Sn, and Nd; The slurry B for forming the Rh-containing coating II includes the following raw materials: modified cerium zirconium powder with high zirconium content, modified zirconium oxide, modified alumina, oxide additive, water, and Rh; wherein the zirconium oxide content in the modified cerium zirconium powder with high zirconium content is 50-70%; the modified cerium zirconium powder with high zirconium content is a cerium zirconium powder with high zirconium content modified by any one or more elements of La, Ba, Y, Pr, Sn, and Nd; The modified polycyclic molecular sieve is a polycyclic molecular sieve modified by any one or more elements of Pd, Pt, Rh, Cu, Fe, Mn, and Co; The modified zirconium oxide is zirconium oxide modified by any one or more elements of La, Ba, Y, Pr, Sn, and Nd, and the content of the modified component is 0.1-40% of the modified zirconium oxide; The modified alumina is alumina modified by any one or more elements of Y, La, Si, Ce, Sr, K, Li, Mg, Sn, and Na, and the content of the modified component in the modified alumina is 10-30%.

2. The chassis catalyst according to claim 1, It is characterized in that The concentrations of the raw materials in the slurry A are as follows: 1-100 g / L of modified low zirconium content cerium zirconium powder, 1-100 g / L of modified alumina, 1-250 g / L of modified polycyclic molecular sieve, and 1-45 g / L of oxide additive.

3. The chassis catalyst according to claim 1, It is characterized in that The concentrations of the raw materials in the slurry B are as follows: 1-50 g / L of modified high zirconium content cerium zirconium powder, 1-50 g / L of modified zirconium oxide, 1-100 g / L of modified aluminum oxide, and 1-45 g / L of oxide additive.

4. The chassis catalyst according to claim 1, It is characterized in that In the modified polycyclic molecule, the content of the modified component in the modified polycyclic molecular sieve is 0-10%, but 0% is excluded; the polycyclic molecular sieve in the modified polycyclic molecular sieve is one or more of BEA, CHA, MOR, MFI, LTA, FAU, MON, AFN, AFT, and AFX type molecular sieves.

5. The chassis catalyst according to claim 1, It is characterized in that In the modified cerium-zirconium powder with low zirconium content, the content of the modified component in the modified cerium-zirconium powder with low zirconium content is 0.1-30%, and the content of zirconium oxide in the modified cerium-zirconium powder with low zirconium content is 20-49.5%.

6. The chassis catalyst according to claim 1, It is characterized in that In the modified cerium-zirconium powder with high zirconium content, the content of the modified component in the modified cerium-zirconium powder with high zirconium content is 0.1-30%, and the content of zirconium oxide in the modified cerium-zirconium powder with high zirconium content is 50-70%.

Citation Information

Patent Citations

  • Vehicle three-way catalytic converter for collecting integrated particulate matters

    CN106050372A

  • Automobile ternary catalytic converter

    CN107790124A

  • Catalyst for GPF (gasoline particulate filter) and preparation method of catalyst

    CN108295851A

  • Lean-burn NOx trapping catalyst improving low temperature NOx conversion efficiency and preparation method of lean-burn NOx trapping catalyst

    CN109675615A

  • Outer-layer Rh coating layer of automobile tail gas purification three-way catalyst and catalyst thereof

    CN110665501A